Extração de compostos bioativos e análise de potencial da atividade antioxidante de seriguela (Spondias purpurea L.) em diferentes estádios de maturação - Barbosa, Paula Ferreira (2020)
The seriguela plant (Spondias purpurea L.) is found in several regions of the world, including in the northeast of Brazil. The pleasant aroma and bittersweet flavor of the fruits are rich in phytochemicals, such as pigments and phenolic compounds. The content of these compounds in fruits can increase, decrease or do not change significantly during ripening, and the determination of the type of solvent in the extraction is necessary for an efficient extraction of phytochemicals. Thus, the present work evaluated the physico-chemical, phytochemical composition and antioxidant activity in the individual parts of the fruit at different stages of maturation. The fruits were selected according to the degree of ripeness (unripe, half-ripe and ripe) and separated into seed, peel and pulp. According to the analyses performed, the results were satisfactory for the physic-chemical characterization, and it was observed that most of the constituents increased during the maturation. As for the total tannins, they are present in greater concentration in the peel and seed in the unripe and half-ripe stages. Analyzing the extraction efficiency of the solvents used, it was clear that the solution containing almost 50% ethanol in an acidified medium showed better extraction power for phenolic compounds and flavonoids ranging from 494.45 to 9760.94 mg EAG / 100 g and total flavonoids from 81.85 to 1760.22 mg EAG / 100 g, in both analyses the highest concentration was in the peel and seed in the green and half-ripe stages, in addition to having excellent antioxidant activity in the ABTS·+ , DPPH· , FRAP assays and ORAC. As for the concentration of ascorbic acid, the highest content was present in the pulps and peel of seriguela. The organic acid profiles showed variations during maturation, with citric, fumaric and succinic acids being identified. As for the profile of sugars identified, fructose was the major sugar in all parts of the fruit, glucose already had a higher concentration was in the seed, while sucrose is present in greater quantity in the pulp, among all the analyzed sugars the concentrations increased during the fruit ripening. The βcarotene carotenoid identified in the HLPC varied from 42.73 to 477.03 μg β-carotene / g, with a higher concentration was in the unripe peel. The phenolic compounds were identified and quantified by UFLC-DAD, totaling 13 compounds, seven phenolic acids, three flavanols and four flavonols. The results showed that the highest concentrations of the compounds were observed in the peel and seed, with the majority being in the green and half-ripe maturation stages. In view of the above, this study can provide information about the seriguela, regarding the composition of phytochemicals, in addition to the individual phenolic compounds present in the fractions of the fruits, which will help in choosing the maturation stage according to the interest of the food and / or pharmaceutical industry.